2016
DOI: 10.1007/s10295-015-1665-y
|View full text |Cite
|
Sign up to set email alerts
|

The many roles of glutamate in metabolism

Abstract: The amino acid glutamate is a major metabolic hub in many organisms and as such is involved in diverse processes in addition to its role in protein synthesis. Nitrogen assimilation, nucleoside, amino acid, and cofactor biosynthesis, as well as secondary natural product formation all utilize glutamate in some manner. Glutamate also plays a role in the catabolism of certain amines. Understanding glutamate's role in these various processes can aid in genome mining for novel metabolic pathways or the engineering o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
102
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(109 citation statements)
references
References 93 publications
(89 reference statements)
3
102
0
4
Order By: Relevance
“…However, glutamate could not mimic the effects of AKG in the protein synthesis of C2C12 myotubes. Previous evidence suggests that glutamate plays a key function in nitrogen assimilation, amino acid biosynthesis, and cofactor production41. Moreover, glutamate reportedly enhances mucosal protein synthesis42.…”
Section: Discussionmentioning
confidence: 99%
“…However, glutamate could not mimic the effects of AKG in the protein synthesis of C2C12 myotubes. Previous evidence suggests that glutamate plays a key function in nitrogen assimilation, amino acid biosynthesis, and cofactor production41. Moreover, glutamate reportedly enhances mucosal protein synthesis42.…”
Section: Discussionmentioning
confidence: 99%
“…7 It has many important functions. 7,8 For example, it can regulate the metabolism of liver and small intestine, and help gut function. 8,9 In addition, it is the essential amino acid for lymphocyte proliferation and secretion.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 For example, it can regulate the metabolism of liver and small intestine, and help gut function. 8,9 In addition, it is the essential amino acid for lymphocyte proliferation and secretion. [10][11][12][13] Previous studies also indicate that glutamine has antioxidant effects and can improve intestinal immunity by stimulating the release of lymphocytes within the intestinal wall.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that glutathione can scavenge peroxides in the body, reduce cellular damage caused by oxygen free radicals, promote repair of damaged cells and increase the antioxidant capacity of the body. The decrease in glutamate indicates that glutathione is reduced, leading to the cell membrane beung damaged, the body being damaged by free radicals and the immunity being decreased (Walker & van der Donk, ).…”
Section: Discussionmentioning
confidence: 99%